Comparative Genomic Analysis of the ICESa2603 Family ICEs and Spread of erm(B)- and tet(O)-Carrying Transferable 89K-Subtype ICEs in Swine and Bovine Isolates in China - Huang, Jinhu; Liang, Yuan; Guo, Dawei; Shang, Kexin; Ge, Lin; Kashif, Jam; Wang, Liping (Frontiers in Microbiology, 2016)
Integrative and conjugative elements (ICEs) of the ICESa2603 family have been isolated from several species of Streptococcus spp.; however, the comparative genomic and evolutionary analyses of these particular ICEs are currently only at their initial stages. By investigating 13 ICEs of the ICESa2603 family and two ICESa2603 family-like ICEs derived from diverse hosts and locations, we have determined that ICEs comprised a backbone of 30 identical syntenic core genes and accessory genes that were restricted to the intergenic sites or the 3′-end of the non-conserved domain of core genes to maintain its function. ICESa2603 family integrase IntICESa2603 specifically recognized a 15-bp att sequence (TTATTTAAGAGTAAC) at the 3′-end of rplL, which was highly conserved in genus Streptococcus. Phylogenetic analyses suggest that extensive recombination/insertion and the occurrence of a hybrid/mosaic in the ICESa2603 family were responsible for the significant increase in ICE diversity, thereby broadening its host range. Approximately 42.5 and 38.1% of the tested Streptococcus suis and Streptococcus agalactiae clinical isolates respectively contained ICESa2603 family Type IV secretion system (T4SS) genes, and 80.5 and 62.5% of which also respectively carried intICESa2603, indicating that ICESa2603 family is widely distributed across these bacteria. Sequencing and conjugation transfer of a novel sequence type ST303 clinical S. suis isolate HB1011 demonstrated that the 89K-subtype ICESsuHB1011 retained its transferrable function, thereby conferring tetracycline and macrolide resistance.